Odpowiedzi

2009-11-21T12:53:07+01:00
H = a√3/2 = 12√3/2 = 6√3cm

a) R = 2/3h = 2/3 * 6√3 = 4√4cm
P = πr² = 64πcm²
Obw = 2πr = 8√3πcm

b) r = 1/3h = 1/3 * 6√3 = 2√3
P = πr² = 12πcm²
Obw = 2πr = 4√3πcm
1 5 1
2009-11-21T13:09:08+01:00
H = a√3/2 = 12√3/2 = 6√3cm

a) R = 2/3h = 2/3 * 6√3 = 4√4cm
P = πr² = 64πcm²
Obw = 2πr = 8√3πcm

b) r = 1/3h = 1/3 * 6√3 = 2√3
P = πr² = 12πcm²
Obw = 2πr = 4√3πcm

Chyba tak :]
Myślę że pomogłem :D
Najlepsza Odpowiedź!
2009-11-21T13:16:43+01:00
H=a√3/2
h=12√3/2=6√3
a)r=2/3h=r=2/3*6√3=4√3
P=πr²
P=(4√3)²π
P=48π cm²
ob=2πr
ob=8√3π cm
b)r=1/3h
r=1/3*6√3=2√3
P=(2√3)²π
P=12π cm²
ob=4√3πcm
1 5 1